African blood group markers in Eti-Turks - Kanra, Tekin; Özsoylu, Şinasi; Işcan, Muzaffer (The Turkish Journal of Pediatrics, 1983)
Blood group phenotypes Fy (a-b-) and Rho, which are considered to be specific African genetic markers, have been sought in 87 Eti-Turks. Overall prevalence of Fy (a-b-) and Rho has been found to be 14.9%. This finding, completely different from that of the general population, documents the African admixture in this ethnic group.
Keywords: African blood group markers; blood group markers and hemoglobin S; Eti Turks; hemoglobin S